Ability to Detect the Linear Attack in Industrial Control Systems by CUSUM Method - Nguyen, Duc Duong; Le, Minh Thuy; Cung, Thanh Long (Old Journal, 2020)
This paper presents the ability to apply the Cumulative Sum (CUSUM) method to detect linear attacks, in case the Kullback–Leibler (K-L) method cannot detect. In order to do this, we investigated to find linear attack matrices, for which the K-L method was surpassed in the range of detection threshold from 0 to 176.76 and applying for heat mixing process, which is used in food plants. Then, the found linear attack matrices were used to find the detection threshold of the CUSUM method. By analyzing the tested results, which is implemented on simulation data, we have determined a suitable range of threshold for CUSUM method to detect linear attacks, when the K-L method is failed to detect.